Emotion-Associated Tones Attract Enhanced Attention at Early Auditory Processing: Magnetoencephalographic Correlates - Bröckelmann, Ann-Kathrin (J Neurosci, 2011)
Emotionally significant objects and events in our environment attract attention based on their motivational relevance for survival. Such kind of emotional attention is thought to lead to affect-specific amplified processing that closely resembles effects of directed attention. Although there has been extensive research on prioritized processing of visual emotional stimuli, the spatio-temporal dynamics of motivated attention mechanisms in auditory processing are less clearly understood. We investigated modulatory effects of emotional attention at early auditory processing stages using time-sensitive whole-head magnetoencephalography. A novel associative learning procedure involving multiple conditioned stimuli (CSs) per affective category was introduced to specifically test whether affect-specific modulation can proceed in a rapid and highly differentiating fashion in humans. Auditory evoked fields (AEFs) were recorded in response to 42 different ultrashort, click-like sounds before and after affective conditioning with pleasant, unpleasant, or neutral auditory scenes. As hypothesized, emotional attention affected neural click tone processing at time intervals of the P20-50m (20–50 ms) and the N1m (100–130 ms), two early AEF components sensitive to directed selective attention (Woldorff et al., 1993). Distributed source localization revealed amplified processing of tones associated with aversive or pleasant compared with neutral auditory scenes at auditory sensory, frontal and parietal cortex regions. Behavioral tests did not indicate any awareness for the contingent CS–UCS (unconditioned stimulus) relationships in the participants, suggesting affective associative learning in absence of contingency awareness. Our findings imply early and highly differentiating affect-specific modulation of auditory stimulus processing supported by neural mechanisms and circuitry comparable with those reported for directed auditory attention.